School Behavior, School Performance, and Race as Focal Concerns in the Institutionalization of Juveniles - Lowery, Patrick Glen (Crime & delinquency, 2025)
According to the focal concerns perspective, the concerns guiding judges’ sentencing considerations are blameworthiness and harm, community protection, and practical considerations. Regarding racial and other disparities in sentencing, focal concerns contend that various constraints, associations between defendants’ demographic characteristics, and the three focal concerns influence judicial decision-making. One association that is explored infrequently is the institutionalization decision of juveniles and how that decision is associated with race and various school-based metrics. Using a sample of adjudicated delinquent juveniles from one state over a 5-year period and merged with American Community Survey data, the present study explores how school factors alongside race serve as focal concerns for judges, impacting the decision to institutionalize juveniles.